Is greed contagious? Four experimental studies. (20th May 2019) - Cardella, Eric; Kugler, Tamar; Anderson, Jennifer; Connolly, Terry
Abstract: Do people become greedier when interacting with others they perceive to be greedy? It has been speculated that greed contagion exits and may have influenced the 2008 financial collapse. We examined this possibility in four experimental studies using a common pool resource dilemma. Specifically, whether participants' second‐round (R2) withdrawal from the common pool was influenced (a) by their assessment of how greedy their opponents' first‐round (R1) withdrawal was, (b) by R1 opponents' reputation for being greedy, (c) by observing past behavior of others in unrelated interactions, and (d) when R1 opponents directly confronted them with an assessment of their own greediness of their R1 withdrawal. In addition, Study 2 examined R2 interactions involving new opponents. Taken together, results suggest that there is contagion of greed. However, the connection appears to be driven by participants adjusting to their opponent's actual behavior, not by their evaluation of the greediness of such behavior. It seems that perceptions of greed do not mediate future behavior and, thus, are not necessarily contagious, but norms of selfish behavior are. In this sense, greed perceptions appear to by epiphenomenal in that they are an incidental by‐product of the behavioral interaction. We discuss the implications of these findings and suggest directions for further research.